Listen up! You're tuning out! emotional triggers that serve as listening barriers in senior populations - Froemming, Kristin J. (My University, 2009)
The United States Census Bureau (2008) projects the number of U.S residents over 65 to more than double from 40.2 million in 2010 to 81.2 million in 2040. This population's rapid growth indicates the importance of dedicating energies toward uncovering ways to more effectively communicate with older adults, including how to prevent them from "tuning out" of a listening interaction. Related to tuning out is the concept of noise which is defined as "factors that interfere with the accurate exchange of messages" (Brownell, 2006, p. 42). Forms of noise, especially behaviors and words, can become "hot buttons" for people. Given the scarcity of scholarly studies on the impact of emotional triggers on listening in the senior population, this study sought to determine how emotional triggers contribute to ineffective listening in older adults. Participants with a mean age of 84 participated in one of four focus groups designed to gain insights into how emotional triggers can provide barriers to effective listening. The results of the focus groups were analyzed using Miles and Huberman's (1994) methods of qualitative data analysis. Results of this study found language barriers to include pause fillers, incorrect word usage, words that implied false familiarity, assumptive words, and poor topic choice. Non-verbal behaviors serving as barriers to effective listening included repetition, poor turn taking skills and the quality of the speaker's voice. Older adult listeners noted that they react to emotional triggers by experiencing the desire to be somewhere else, feelings of guilt, and a drifting mind. A deeper understanding of how the older individual perceives his or her own listening ability and effectiveness is an important step in offering them, and those with whom they interact, information that is practical and appropriate.
This file was last viewed in Adobe Reader 9.0
Keywords: Listening; Older people -- Communication; Emotions